Are school physical activity characteristics associated with weight status in primary school children? A multilevel cross-sectional analysis of routine surveillance data. Issue 2 (23rd October 2013) - Pallan, Miranda J; Adab, Peymane; Sitch, Alice J; Aveyard, Paul
Abstract : Background: The school environment potentially influences the development of childhood obesity. Changes to schooling could be used as an intervention to reduce obesity but the features of the school environment that influence obesity are unknown. Aim: To estimate the interschool variation in body mass index (BMI) z-scores in primary school children and examine the individual and school physical activity characteristics contributing to this. Methods: Cross-sectional analysis and multilevel modelling at individual and school level, with BMI SD scores (z-scores) as the outcome. Individual and school data were obtained for 11 118 reception year children (age 4–5) and 10 151 year 6 children (age 10–11) from 296 primary schools in Birmingham. Data sources were the UK National Child Measurement Programme and the annual National School Sport Survey in 2006/7. Results: In reception year children, 4.2% of the variation in BMI z-scores is attributed to differences between schools. Individual characteristics explained 24% of this between-school variation and certain school physical activity characteristics (the time schools devote to physical education) explained a further 28%. In year 6 children, only 0.9% of the variation in BMI z-scores was between-school variation. BMI z-scores were significantly higher in year 6 than reception year children, with the largest increases between year groups in the South Asian and African-Caribbean ethnic groups. Deprivation was positively associated with BMI z-scores. Conclusions: In addition to the association between individual characteristics and BMI z-score, there is a small but significant association between school characteristics and BMI z-score, which is in part explained by the time schools devote to physical education. This modest school effect has the potential to have a substantial impact on children's weight status at a population level.